Pelatihan Pembuatan Sabun Cuci Piring Dalam Rangka Pemberdayaan Perempuan di Kecamatan Tanjung Mutiara Kabupaten Agam - Sahaq, Anang Baharuddin; Permadani, Resi Levi; Anwar, Syamsul; Sutri, Reni; Jaeba, Kushisa Atta; Yanti , Lusi Rahma (Politeknik ATI Padang, 2023)
Most of the residents of Tiku V Jorong Village, Agam District work as farmers and gardeners, whereas the women mostly are housewives. The training given to women community in Tiku V Jorong Village was the production of liquid dish soap. The selection of liquid dish soap products is based on the fact that consumption of dish soap is always needed by every household in their daily life. In addition, the process of making liquid dish soap is relatively easy and the process does not require many equipment, thus it can be done by women community in Tiku V Jorong Village on the sidelines of other daily activities.The liquid dish soap can be used for their daily needs or can be business opportunities for the village. The activity was carried out on November 26, 2022, which was attended by ± 25 women. The training began with the explanation about the materials and equipment used in making the liquid dish soap. The main materials used were texapon, sodium sulfate, and sodium chloride. Foam booster, perfume, and dye were used as additive. Then, the practice is carried out jointly between the women community and the community service team from Politeknik ATI Padang, thus the women community can be able to make the liquid dish soap on their own. The training was closed with the presentation of business prospective from liquid dish soap. All of the participants were enthusiastic with this training. With this training, it can be expected that the women community in Tiku V Jorong Village have the knowledge and the skill to make their own liquid dish soap. Besides, it can be the new opportunity for business thus the local economy can be improved as well.